Penyelesaian Konflik Antar dan Intern Agama Dengan Surat Keputusan Bersama - Budiantoro, Totok; Hardyansah, Rommy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The state guarantees the freedom for every citizen to embrace a religion and practice their worship. However, problems that arise in life between religious communities are always there. The conflict takes a lot of energy and thought from all parties because it has touched on the political, social, and economic realms. The government has made various efforts to reduce conflict between religious communities, such as conducting interfaith dialogue. It is hoped that the community can prepare themselves to hold discussions with people of other religions who have different views on the reality of life. The dialogue is intended to get to know each other and gain new knowledge about the religion of the dialogue partner. The dialogue itself will enrich the insights of both parties in order to examine the similarities that can be used as a basis for living in harmony in society.